Modeling Interprovincial Cooperative Carbon Reduction in China: An Electricity Generation Perspective - Zeng, Lijun; Du, Wenjing; Zhao, Laijun; Sun, Zhimei (Frontiers in Energy Research, 2021)
As the world faces great challenges from climate change, carbon reduction has become China’s basic national policy. However, the non-cooperative carbon reduction model (NCCRM), the simple regulation mode that is China’s main model for carbon reducing, is not beneficial for optimization of electricity generation capacity structure, and cannot effectively motivate carbon reducing at the provincial level. Therefore, we propose an interprovincial cooperative carbon reduction model (CCRM) from the perspective of electricity generation, which provides a mechanism integrating two fundamental principles of efficiency and fairness. The CCRM consists of two parts: (1) an optimal model of carbon reduction with the object of minimizing the carbon emission of the cooperation union to determine the optimal annual electricity generation for each participating province; and (2) a model that distributes the economic benefits of the cooperation among the provinces in the cooperation based on the Shapley value method. We applied the CCRM to the case of an interprovincial union of Shanghai, Sichuan, Shanxi, and Gansu in China. The results, based on the data from 2001–2014, show that cooperation can significantly reduce the carbon emission of the union by 840.67× 108kg, 21.48%; meanwhile, Shanghai, Sichuan, Shanxi, and Gansu can respectively get 6.73× 108, 29.93× 108, 14.93× 108, and 59.02× 108 CNY of extra benefits from carbon reduction. To test the impact of different parameter values on the results of the CCRM, a sensitivity analysis was conducted. Some policy recommendations are proposed to promote the implementation of the CCRM.